Non-Covalent Functionalization of Magnetic Carbon Nanotubes with Fmoc Amino Acid-Modified Polyethylene Glycol - BATIREL, SAİME (My University, 2024)
Once dispersion and cytotoxicity issues are resolved, it has been proven that carbon nanotubes (CNTs) have great advantages in biomedical applications due to their unique properties. In this study, the superiority of carbon nanotubes was combined with magnetic targeting strategies, and a solution to the distribution problem in the aqueous media of the resulting CNTs decorated with iron oxide (mCNTs) was sought. A non-covalent functionalization approach has been utilized to overcome this fundamental drawback of mCNTs. Conjugates of polyethylene glycol monomethyl ether and 9- fluorenyl methyl chloroformate (Fmoc) amino acids were used to coat the lateral surfaces of mCNTs, making them more water-soluble. The selected Fmoc amino acids have different numbers of aromatic rings, which is known to affect the coating efficiency in non-covalent functionalization and therefore, the dispersion behavior of the CNTs. Their coating yields, dispersion behaviors, magnetism, charge, and size properties have been determined. All coated mCNT samples displayed superparamagnetic behavior. Dispersion tests showed a promise to increase the stability of mCNTs with this approach. Moreover, we demonstrated that the functionalization of mCNTs affects cell viability in a dose-dependent manner. The main finding of this study is that mCNTs can be successfully functionalized with Fmoc amino acid-modified polyethylene glycol.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; ENERJİ VE YAKITLAR; MALZEME BİLİMİ, BİYOMATERYAL; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; ENERGY & FUELS; MATERIALS SCIENCE, BIOMATERIALS; MATERIALS SCIENCE, MULTIDISCIPLINARY; Biyomalzemeler; Fizik Bilimleri; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Enerji Mühendisliği ve Güç Teknolojisi; Malzeme Kimyası; Biomaterials; Physical Sciences; Renewable Energy, Sustainability and the Environment; Energy Engineering and Power Technology; Materials Chemistry; Fmoc amino acid; Iron oxide; Polyethylene glycol; Single-walled carbon nanotube; Surface functionalization